2014
DOI: 10.1017/s1751731113001924
|View full text |Cite
|
Sign up to set email alerts
|

The use of stoned olive cake and rolled linseed in the diet of intensively reared lambs: effect on the intramuscular fatty-acid composition

Abstract: The aim of the present study was to evaluate the effect of the inclusion of stoned olive cake and rolled linseed in a concentratebased diet for lambs on the fatty-acid composition of polar and non-polar intramuscular lipids of the longissimus dorsi muscle. To achieve this objective, 32 Appenninica lambs were randomly distributed into four groups of eight lambs each and were fed conventional cereal-based concentrates (diet C); concentrates containing 20% on a dry matter (DM) basis of rolled linseed (diet L); co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
45
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 36 publications
(60 reference statements)
15
45
2
Order By: Relevance
“…Some authors found an increase of LC-PUFAn-3 in lambs fed linseed diets (Noci et al, 2011;Berthelot et al, 2012), while others did not observe any effect (Bas et al, 2007). Others found that feeding ewes a n-3-enriched diet in lactation increased the proportion of 18:3n-3 and their longer chain derivatives in suckling lamb muscles (Gómez-Cortés et al, 2014;Mele et al, 2014), whereas Berthelot et al (2012) did not report such effects in their earlier experiment. Some studies in human and laboratory animals suggest that the conversion of ALA into LC-PUFA homologs increases during pregnancy probably due to the agonistic effects of the female sex hormones estrogen and progesterone (Kitson et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Some authors found an increase of LC-PUFAn-3 in lambs fed linseed diets (Noci et al, 2011;Berthelot et al, 2012), while others did not observe any effect (Bas et al, 2007). Others found that feeding ewes a n-3-enriched diet in lactation increased the proportion of 18:3n-3 and their longer chain derivatives in suckling lamb muscles (Gómez-Cortés et al, 2014;Mele et al, 2014), whereas Berthelot et al (2012) did not report such effects in their earlier experiment. Some studies in human and laboratory animals suggest that the conversion of ALA into LC-PUFA homologs increases during pregnancy probably due to the agonistic effects of the female sex hormones estrogen and progesterone (Kitson et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…The detailed animal management and diet composition was published by Luciano et al (2013) and by Mele et al (2014). Briefly, the feeding trial was conducted at the Experimental Station of the Department of Applied Biology at the University of Perugia, Italy and involved 32 Appenninica male lambs.…”
Section: Animals and Dietary Treatmentsmentioning
confidence: 99%
“…Recently, we have conducted a study to increase the concentration of PUFA n-3 fatty acids in lamb meat by feeding diets containing linseed (Mele et al, 2014). Considering that PUFA n-3 fatty acids are susceptible to oxidation, we have added olive cake into the diets and we found that the combination of linseed and olive cake effectively increased the content of n-3 PUFA in the muscle (Mele et al, 2014) and preserved the meat from rapid oxidation (Luciano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations